Three‐ to Four‐Year‐Old Children Rapidly Adapt Their Predictions and Use Them to Learn Novel Word Meanings. Issue 1 (13th July 2018) - Havron, Naomi; de Carvalho, Alex; Fiévet, Anne‐Caroline; Christophe, Anne
Abstract : Adults create and update predictions about what speakers will say next. This study asks whether prediction can drive language acquisition, by testing whether 3‐ to 4‐year‐old children ( n = 45) adapt to recent information when learning novel words. The study used a syntactic context which can precede both nouns and verbs to manipulate children's predictions about what syntactic category will follow. Children for whom the syntactic context predicted verbs were more likely to infer that a novel word appearing in this context referred to an action, than children for whom it predicted nouns. This suggests that children make rapid changes to their predictions, and use this information to learn novel information, supporting the role of prediction in language acquisition.